Nanocarreadores biopoliméricos de isoflavonas de soja e óleos essenciais: potencial dermocosmético, fotoprotetivo e antimicrobiano - Santos, Eduarda Oliveira dos (2023)
With the emergence of healthier and more conscious lifestyles, the cosmetics market has undergone a significant shift in chemical reformulation and technological planning. Plant extracts and essential oils stand out, as their components can exhibit more than one of these characteristics simultaneously and act synergistically. The strategy of converting regular materials into nano-scale formulations for cosmetics lies in formulating products with a high penetration power into the skin layers. Thus, this study aims to evaluate the potential of secondary metabolites found in soybean seeds (Glycine max) and commercially sourced essential oils (Geraniaceae, Pinaceae, and Citrae) as agents for dermocosmetic application, based on antimicrobial, antioxidant, and photoprotective activities, and the production of nanocapsules using biodegradable polymer. For this purpose, quantitative extraction of phenolic compounds restricted to legumes (Fabaceae), the aglycone isoflavones daidzein, glycitein, and genistein was performed. The identification and quantification of active compounds were obtained through UHPLC-ESI-QTOF-MS, HPLC-UV/DAD, and GC-MS. Finally, the samples were nanoencapsulated using polycaprolactone. The colloidal suspension obtained was characterized based on zeta potential, pH, particle diameter, and encapsulation efficiency, as well as the efficiency of the spray-drying process. The soy extract prepared using an EtOH:DMSO 80% solution with ultrasound assistance proved to be more efficient in extracting daidzein, glycitein, and genistein (58.0 ± 4.33; 7.37 ± 0.575; 61.9 ± 4.06 mg/100 g respectively) with better photoprotective activity (MEC = 0.482 ± 0.018 mg/mL) and antioxidant activity (9.2 mg GAE/100g; IC50= 1.36 mg/mL). Daidzein and genistein standards showed better photoprotective activity compared to the benzophenone control. Geranium essential oil (Pelargonium graveolens) stood out as an antimicrobial agent (IC50= 5.63 µL/mL; SI=1.68), cedar essential oil (Cedrus atlantica) as a photoprotective agent (MEC = 6.6 µg/mL), and tangerine oil (Citrus reticulata) as an antioxidant (30.9 mg GAE/g). The major components were identified as citronellol for geranium oil, himachalene for cedar oil, and limonene for tangerine oil. The prepared nanocarriers had an average particle diameter of 300 nm, a zeta potential of -20 mV, and IPD between 0.3 and 0.5, demonstrating relative stability regarding the evaluated hydrogenic potential. The encapsulation efficiency was determined in terms of daidzein and genistein isoflavones, with values above 90%, and a drying efficiency of 52%. This work demonstrated the potential of soy isoflavones and essential oils as powerful photoprotective and antimicrobial agents, as well as the feasibility of their incorporation in the form of nanocarriers as potential dermocosmetic agents.